Navigating The World Of Tourism: A Literature Review Of English Language Proficiency's Influence - Shella Gherina Saptiany; Tiara Sanika Langsa Putriningsih (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research article provides a comprehensive literature review examining the key role of English proficiency in the tourism sector. Using a literature review method, the researchers summarize the results of 20 articles from renowned journals, providing a comprehensive analysis of the impact of English language skills on the tourism industry. The analysis spans a large body of literature and examines how English proficiency affects various aspects of tourism, including tourist satisfaction, destination preferences, employment prospects, and global destination competitiveness. There are three themes that the researchers found from the analysis of the journals, first Language as a Medium of Tourism Communication, English Specific Purpose of Tourism, Cross-Cultural Comprehension and Cultural Awareness, and Online Advertising and Promotion. The researchers shed light on the various ways in which language skills shape tourism dynamics. This analysis shows that a good command of the English language is a crucial factor for both tourists' experiences and the success of tourism businesses. It shows how language skills have a significant impact on communication, improving tourist enjoyment and promoting greater economic profitability in the tourism sector. This research highlights the importance of English proficiency in the global tourism landscape and illuminates the dynamic interaction between language and the tourism experience.